Heads or tails: how do chemically substituted fullerenes melt?. Issue 26 (18th April 2016) - Armstrong, Jeff; Mukhopadhyay, Sanghamitra; Bresme, Fernando; Fernandez-Alonso, Felix
Abstract : The melting of the substituted fullerene PCBM is driven by the tail, not the head. Abstract : We address the question as to whether the melting of chemically substituted fullerenes is driven by the dynamics of the fullerene moiety (the head) or the substituted sub-unit (the tail). To this end, we have performed quasielastic neutron-scattering experiments and classical molecular-dynamics simulations as a function of temperature on the prototypical fullerene derivative phenyl-C61-butyric acid methyl ester. To enable a direct and quantitative comparison between experimental and simulation data, dynamic structure factors for the latter have been calculated from atomic trajectories and further convolved with the known instrument response. A detailed analysis of the energy- and momentum-transfer dependence of this observable in the quasielastic regime shows that melting is entirely driven by temperature-activated tail motions. We also provide quantitative estimates of the activation energy for this process as the material first enters a plastic-crystalline phase, followed by the emergence of a genuine liquid at higher temperatures.